A retrospective comparative analysis of the maternal and child health MDGs in Rwanda, Burundi and Uganda: Beyond 2015 - Ntukanyagwe, Michelle M. (Graduate School of Development Policy and Practice, 2020)
The timeline of the Millennium Development Goals (MDGs) elapsed in 2015, global indicators showed that Africa still accounts for almost half of all child deaths globally and has the world’s highest maternal mortality rates. By the year 2015, Africa as a continent was unable to meet the maternal and child health MDG targets. This study seeks to retrospectively compare, the progress made on the maternal and child health related Millennium Development Goals namely: MDG4- Reduce child mortality and MDG5- Improve Maternal Health, in Burundi, Rwanda and Uganda. Indicators show that, only Rwanda was able to achieve the maternal and child health MDGs. Specifically, the study provides a contextual understanding of the policy interventions implemented by Rwanda, despite starting from a lower base in comparison to Burundi and Uganda due to the 1994 Genocide against the Tutsi. The study also sought to understand how broad governance indicators specifically, government effectiveness and control of corruption vary between the three countries: Rwanda, Burundi and Uganda as well as their impact on maternal and child health trends. The study illustrates how Rwanda’s governance is underpinned by a system that is strongly hinged on ideological clarity, good leadership, country ownership for effective policy execution and enforcement of accountability through home grown solutions like imihigo. The integration of imihigo within the health sector has, in addition to other innovative interventions, like the implementation of the Community Health Insurance Policy, deployment of over 60,000 community health workers, innovative use of ICT in health like rapid short message service (sms), drones among others. In contrasting the governance of the health sectors in Rwanda and Uganda, one of the striking differences is that in Rwanda, there are strong linkages between the local and central levels for policy implementation and evaluation, and between the health sector and finance ministry. These are indicative of strong intra-governmental accountability. Uganda on the other hand, despite having good laws and policies in place, still faces poor implementation and lack of strong accountability mechanisms, due to low levels of ownership. The contrast is also sharply illustrated by Rwanda’s higher score in the indicative measures of “government effectiveness and control of corruption”. In short, better quality governments usually have positive effect on development outcomes thanks to overall efficiency in the delivery of public services. Specific recommendations include for Uganda to generate good local governance, effective implementation of decentralisation, follow through of policies and enforcement of accountability for performance failures, the use of community health workers to address existing scarcity of health sector personnel as well as the adoption of ICT policies to support the implementation of health interventions.